PENGARUH STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Komang Tri Wahyuni (Jurnal Nirta : Inovasi Multidisiplin, 2023)
`This study is conducted to analyze the impact of ownership structure on value of the firm. Dimensions of ownership structure are represented by concentrated ownership and managerial ownership. The samples of this study are LQ45 companies listed on the Indonesian Stock Exchange (IDX) for the periode 2016-2020 . Total Observation of 125 was determined by purposive sampling method. Both market based value measure: PER and PBV are used to measure value of the firm. There is market capitalization as a control variables. This study uses Ordinary Least Square (OLS) for hypotheses testing The results show that Ownership concentration have a positive effect with statistical significance on value of the firm (market performance). Managerial ownership was found to have a negative effect with statistical significance on value of the firm (market performance), and also size of the firm effect have a positive effect with statistical significance on valuation PER and negative on valuation PER. The implication of this study showed that all companies should concentrated ownership which creates majority and minority shareholders creating a potential conflict that may effect the value of the firm.